Gait patterns in twins with cerebral palsy: similarities and development over time after multilevel surgery - Drongelen, Stefan van; Dreher, Thomas; Heitzmann, Daniel; Wolf, Sebastian Immanuel (Research in developmental disabilities, 2013)
To examine gait patterns and gait quality, 7 twins with cerebral palsy were measured preoperatively and after surgical intervention. The aim was to study differences and/or similarities in gait between twins, the influence of personal characteristics and birth conditions, and to describe the development of gait over time after single event multilevel surgery. A standardized clinical exam and a three-dimensional gait analysis were performed. Gait patterns were classified according to Sutherland and Davids, and the Gillette Gait Index was calculated as a global measure of the gait impairment. Next to subject characteristics at time of first measurement, and at time of birth, birth conditions were collected. Gait patterns were determined as crouch gait in 13 legs, as stiff gait in 6 legs and as jump gait in 8 legs. One leg showed a normal gait pattern. The knee flexion-extension angle correlated most constant with the knee flexion-extension angle of the contralateral leg (range 0.91-0.99). Correlations with the legs of the sibling showed variable correlations (range 0.44-0.99); with all other legs medium to high correlations of 0.73-0.91 were found. The Gillette Gait Index was found to initially decrease after surgical intervention. Similar correlations were found between twins or between legs for the gait pattern expressed by the knee flexion-extension angle, and the Gillette Gait Index improved after surgery. It seems that gait quality in twins with cerebral palsy is characterized predominantly by the traumatic disorder: genetic dispositions and personal characteristics only play a negligible role.